Intrarenal venous flow patterns and their association with successful fluid removal in critically ill patients: a prospective observational exploratory study - Maluangnon, Chailat; Saokaew, Apatsara; Rojwatcharapibarn, Satit; Ratanarat, Ranistha (The Ultrasound Journal, 2025)
Background: Determining the optimal timing for fluid removal in critically ill patients remains a challenge. This study evaluated the utility of Doppler ultrasound, specifically intrarenal venous flow (IRVF) patterns and venous excess ultrasound (VExUS) scores, and their associations with fluid removal outcomes, hemodynamic parameters, and clinical endpoints. Methods: In this prospective observational exploratory study, 52 intensive care unit (ICU) patients who underwent fluid removal were enrolled. Baseline IRVF patterns and VExUS scores were assessed, with follow-up evaluations performed daily for three days. The primary outcome was to evaluate whether IRVF patterns were associated with successful fluid removal, defined as achieving a negative fluid balance for at least two consecutive days. Secondary outcomes included associations with central venous pressure (CVP), NT-proBNP, cumulative fluid balance, and clinical outcomes. Results: Thirty-one patients (59.6%) achieved successful fluid removal. A discontinuous baseline IRVF pattern was independently associated with successful fluid removal (adjusted odds ratio 4.31, 95% CI 1.02–18.18; P = 0.047). This pattern demonstrated high sensitivity of 87.1% (95% CI 70.2–96.4), moderate specificity of 42.9% (95% CI 21.8–66.0), and accuracy of 69.2% (95% CI 54.9–81.3). VExUS scores grades 2–3 demonstrated high specificity of 85.7% (95% CI 63.7–97.0) but low sensitivity of 29.0% (95% CI 14.2–48.0), with an accuracy of 51.9% (95% CI 37.6–66.0). An improvement in the IRVF pattern was significantly correlated with a reduction in NT-proBNP levels (P = 0.048). However, neither IRVF patterns nor VExUS scores improvements were associated with changes in fluid balance, CVP, or clinical outcomes such as 28-day mortality, ventilator-free days, or ICU length of stay. Conclusions: Discontinuous IRVF patterns at baseline were significantly associated with fluid removal success, representing a physiologically based marker for deresuscitation readiness. More large-scale studies are warranted to validate these findings and explore long-term implications. Trial registration ClinicalTrials.gov identifier NCT06216119. Registered 22 January 2024, https://clinicaltrials.gov/study/NCT06216119